Analysis Awkward Posture at Food Production Activity using RULA Assessment - Saiful Bahri, Mohamed; S. A., Syed Ali; S. R., Kamat (2018)
If the workers continuously perform the activities throughout the working hours, they may experience prolonged standing which creates fatigue and causes an occupational hazard which includes slips and falls. The goal of this study was to identify awkward postures during food production activities. 40 workers with minimum of 1 year experience working in food production were involved. The comfort level was measured using Rapid Upper Limb Assessment and Computer-Aided Three-Dimensional Interactive Application software analysis, expressed in scoring level. Critical activities grilling meat, frying, dish cloth and wash utensil at food production contributed to high RULA score of 7. The specific working postures have to be identified among food production workers. This study can provide a preliminary data to determine the correct working postures for food production workers.